SHM_1227498_HST_3D Pointed-Butted Flint Axe - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a pointed-butted flint axe from the Swedish Neolithic, collected in Hallsberg Parish in Närke and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=405

Link to Sök I Samlingarna

https://samlingar.shm.se/object/BF0EE8FF-E2E9-43E4-B577-37CD88B3EABE
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Structured Light Scanning; 3D Model; Museum Object; Dynamic Collections; Swedish Neolithic; Hallsberg; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi